Representação de professor em as aventuras de telêmaco: material de instrução no Lycêo Parahybano (1836 a 1853) - Silva, Hélcia Macedo de Carvalho Diniz e (2019)
This investigation has the objective to analyze the representation of the teacher in the book The Adventures of Telemachus, the Son of Ulysses, by François de Salignac de la Mothe Fénelon, which circulated on Brazilian Empire (1822-1889) and on Parahyba (1836-1853), at the Lycêo Parahybano. For this purpose, it was determined that there was the encyclopedic professor, and that the referred book was present in the referred school, which in Abreu’s (2003) classification, is a reading book (ABREU, 2003), on Bhaktin’s (2003), a book that belongs to the class of romance and education and, in this work, receives the classification of an instruction material. Between the innumerable professors and their practices to make Brazil’s education effective, the building of schools, the equipment and the book as a base to the classes were the means used by the political elite and literate people. Therefore, the presence of the reading book in the schools worked as an instrument to effectiveness, example given, the teaching of translation from French to Portuguese. When analyzing the book, it was verified that it inserts itself on the tradition of the elaborated to instruct the prince, that in the 1800’s was disseminated for all Europe and the world. In the Brazilian Empire, it was adopted in Lycêo Parahybano, on the French subject. From this analysis, it was concluded that the translation teaching by using Literature texts, with philosophical imprint, presents the perspective of working the good behaviors and the art of the well governing, reaching the philosophical dimension of the teaching of ethics and moral, by submitting the readers to the reading of adventures that register events involving Ulysses’ young son and his professor, Mentor, that confronts each challenge, by learning with the mistakes and observing the rules to the good combat. The spontaneity to have relations with the other and the recognizing of the limitations presented by the book’s characters, serve as an instruction to the more cautious reader. The encyclopedic teaching model lasted for the whole Brazilian Empire, when the teaching was exercised by a professor that watched the student, almost as individually, just as Minerva, in the teacher’s person, accompanied Telemachus in every adventure in order to teach what was beyond the book, to know, to be an honored man, happy to know how to govern Ítaca’s place.